Effects of cluster sets and rest-redistribution on mechanical responses to back squats in trained men - Tufano, J. J.; Conlon, J. A.; Nimphius, S.; Brown, L. E.; Petkovic, A.; Frick, J.; Haff, G. G. (Journal of Human Kinetics, 2017)
Eight resistance-trained men completed three protocols separated by 48-96 hours. Each protocol included 36 repetitions with the same rest duration, but the frequency and length of rest periods differed. The cluster sets of four (CS4) protocol included 30 s of rest after the 4th, 8th, 16th, 20th, 28th, and 32nd repetition in addition to 120 s of rest after the 12th and 24th repetition. For the other two protocols, the total 420 s rest time of CS4 was redistributed to include nine sets of four repetitions (RR4) with 52.5 s of rest after every four repetitions, or 36 sets of single repetitions (RR1) with 12 s of rest after every repetition. Mean (MF) and peak (PF) force, velocity (MV and PV), and power output (MP and PP) were measured during 36 repetitions and were collapsed into 12 repetitions for analysis. Repeated measures ANOVA 3 (protocol) x 12 (repetition) showed a protocol x repetition interaction for PF, MV, PV, MP, and PP (p-values from <0.001 to 0.012). No interaction or main effect was present for MF. During RR1, MV, PV, MP, and PP were maintained, but decreased throughout every 4-repetition sequence during CS4 and RR4. During CS4 and RR4, PF was less following a rest period compared to subsequent repetitions, whereas PF was maintained during RR1. These data indicate that rest redistribution results in similar average kinetics and kinematics, but if total rest time is redistributed to create shorter but more frequent sets, kinetics and kinematics may remain more constant.